THE TRAINED BRAIN AND CONSUMER BIAS: IMPACT OF NEUROCOGNITIVE TRAINING ON IMPULSE BUYING TENDENCIES - Khatwani, Monika; Parmar, Anjali (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
Objectives: The research examines the impact of neurocognitive training in helping to reduce impulse buying tendencies (IBT) in young adults (ages 18 to 25). Impulse buying may be triggered by cognitive and emotional triggers and is typically characterised by spontaneous and unplanned purchases. Neurocognitive training enhances cognitive and executive function like impulse control, working memory, and attention regulation and was used as an intervention as a way to reduce such behaviours. Methods: A sample of 120 participants (60 males and 60 females) completed pre- and post-intervention assessments using standardized measures of IBT. Results: Paired sample t-tests demonstrated a statistically significant reduction in scores for males (t = 13.09, p < .001) and females (t = 11.12, p < .001) with large effect sizes (Cohen’s d = 1.32 for males and d = 1.41 for females). The intervention showed a 100.0% improvement rate, and both males (19.0%) and females (19.3%) showed clinically meaningful reductions in IBT. An independent samples t-test indicated that there was no significant difference between the males and females in the effectiveness of training (t = 1.42, p > .05). Conclusion: These figures indicate that neurocognitive exercise is a very effective, and the penis is neutral, intervention to reduce the behavior of buying impulses between young adults. Although these findings must be pushed and repeated, they will benefit the consumer initiatives and programs that teach economic self-regulation techniques. Public importance statement: This research has underlined how neurocognitive training can significantly reduce the impulse buying behaviour in young adults. Intervention that promotes cognitive control and attention regulation via neurocognitive training can promote healthy financial behaviour and help in nurturing long-term consumer welfare. These findings can help in creating educational and consumer programs aimed at economic self-regulation among the youth population.